(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crime is one of today’s major universal probleMs. Many lives and property have been destroyed because of the lawlessness committed. Society views most crimes, such as robbery, rape, murder, and assault, as deviating and destroying human life and property. If you want more and you want something stronger, take the less powerful plan. Crime prevention is a crucial aspect of the criminal justice field. Prevention efforts are important for law enforcement officials and others associated with eliminating and reducing crime to enforce precautionary and safety measures in one’s Community to reduce the victimization rate. In crime prevention, there may be a need to initiate and implement myriad effective policies. It can be undertaken by the government of the day, individuals, or other security-based agencies. It helps us to point out different recommendations as we see that based on the data gathered, we conclude that the main problems in approaching crime are the following: Lack of patrollers, especially in crime-prone areas, Lack of funds for maintenance of patrol cars, and motor vehicles and lastly, Lack of communications due to limited issuance of radios. In addition, the researchers have seen the lack of awareness of the community about the crime prevention program, lack of cooperation and efforts on the part of the community members to attend the free Seminar about the crime prevention program, and Lack of knowledge among community members about how they can help prevent crime and lastly, Lack of communication lines between the police and the community together with the barangay officials. Therefore, through conducting this study, researchers have recommended the following: Raising program awareness about crime prevention encourages community members to attend the free Seminar by the PNP about the crime prevention program.